Handbook of practical electrical design - McPartland, Joseph F (McGraw-Hill NEC series., 1999)
Fully updated to reflect the 1999 NEC®, this new edition provides today's most comprehensive and unified coverage of electrical design. Organized to follow the stages of a typical electrical design job, it clearly explains all facets of electrical design and all the latest practical procedures, practices, and trends involved in the design of electrical systems in commercial, industrial, institutional, and residential occupancies. This illustrated resource features step-by-step details on how to size, select, and apply conductors, raceways, switches, fuses, and all other related system components. It also presents information in a manner that makes it easy for designers to prepare plans and electrical specifications for installers. Packed with design examples and practical pointers, this timesaving and moneysaving new edition of the Handbook addresses all the everyday needs of today's electrical designers.